Macro Issues of Urban and Rural Development and Land Use Planning in the Horizon of Iran 1420 with Strategic Future Approach - Aliakbar Jafarloo; Monireh Ghofran; Sahar Nazari (تحقیقات کاربردی علوم جغرافیایی)
Given the recent challenges faced by urban and rural areas in Iran, it is anticipated that these regions will encounter significant uncertainties and critical issues in the coming years. Addressing land use and mitigating the challenges associated with urban and rural development necessitates a thorough identification of these issues, followed by strategic planning aimed at alleviating their impact. This research adopts a futuristic perspective and employs a qualitative-descriptive methodology to investigate these matters. To achieve the research objectives, an extensive review of relevant literature and library studies was conducted, supplemented by consultations with 70 experts across various domains. This process facilitated the identification of the primary challenges related to urban and rural development and land use within the context of Iran in the year 1420 (Islamic calendar). Subsequently, qualitative analysis was utilized to develop strategic scenarios aimed at addressing the identified challenges in the country’s future trajectory. The findings reveal that Iran will likely experience sudden disruptions and heightened uncertainties, compounded by economic, social, political, environmental, demographic, geopolitical, and climate-related factors, as well as issues related to cyberspace and increasing inequalities. Furthermore, there are unanticipated and unaddressed threats on the horizon. In response to these challenges, twenty future scenarios were devised, designed to confront the macro-level issues highlighted in the research, while also challenging current assumptions and posing critical questions regarding the nation's future. These scenarios provide strategic insights into how Iran can prepare to meet the evolving needs of its urban and rural communities as the country approaches the year 1420, in light of a dynamic and uncertain future.